Identification of fallopian tube stem cells using patient-derived organoids - Alsaadi, A (2021)
Ovarian Cancer is the fifth most common cancer in women. High Grade Serous Ovarian Cancer (HGSOC) presents as the most aggressive histotype, accounting for over 70% of cases. Survival from HGSOC is amongst the lowest for any cancer. Unfortunately, over 70% of patients present at late stages, when 5-year survival verges at a dismal 10-25%. Although the tissue-of-origin of HGSOC is now known to be the Fallopian Tube (FT), the cell-of-origin remains obscure. HGSOC precursor lesions almost always arise in the distal FT, a site reported to be enriched in stem-like cells. Interrogation of HGSOC initiation has been hampered by the lack of appropriate, physiologically relevant models of the FT. Investigation of FT stem cells as the cell-of-origin of HGSOC could not be undertaken, as FT stem cells remain to be identified.